Demanda de dinero intertemporal con generaciones yuxtapuestas - Roca Garay, Richard (2013)
This paper presents the Samuelson’s Model of Overlapping Generations demand for money in wich each period coexist different generations with limited life. Money is the only lasting asset that agents can maintain to purchase when they are in the retirement stage.